Bistable dual-responsive azobenzene-co-PNIPAM soft microactuators via two-photon direct laser writing - Barwig, Chantal; Colaco, Ruchira; Koch, Alina-Sophie; Geiger, Sophie; Curticean, Ernest Ronald; Wacker, Irene; Wang, Zhe; Schmidt, Målin; Sonn, Annabelle; Pashapour, Sadaf; Taheri, Fereydoon; Schröder, Rasmus R.; et al. (Advanced intelligent systems, 2025)
Miniaturized bistable actuators are of notable relevance for applications in microfluidics or the manipulation of delicate objects. Many applications require actuators to be multistable, meaning that they can hold specific positions without continuous energy input. However, reversibly controllable soft actuators, especially those based on thermoresponsive materials, typically lack this capability. To overcome this challenge, bistable soft microactuators fabricated by two-photon polymerization at micrometer precision are demonstrate here, allowing for arbitrary 3D shapes. The bistability is given by material composition, that is, poly(N-isopropylacrylamide) (pNIPAM) and a light-responsive azobenzene compound. The incorporation of an azobenzene into pNIPAM photoresin enables the modification of its lower critical solution temperature (LCST) through the (E)-(Z)-isomerization, allowing for two states: a swollen and shrunken state. Hereby, actuation, in terms of shrinking and swelling, is controlled by photoswitching, allowing for the actuation of Azo_pNIPAM microactuators within a constant ambient temperature regime. Moreover, the pNIPAM moiety also allows thermal actuation when it contains either isomer, ((E) or (Z)), when the ambient temperature exceeds the LCST. Temperature and light changes are applied to characterize the bistable nature of the microactuators and an application of those bistable microactuators in a lab-on-a-chip device is shown.
Gesehen am 02.02.2026